AN ECRANIZATION PROCESS AS SEEN IN THE NOVEL THE FROG PRINCE INTO THE MOVIE - Elia Saroh; Ch. Evy Tri Widyahening (English Education Department Slamet Riyadi University Surakarta, 2023)
This study aims to analyze the form of ecranization the novel entitled “ The Frog Prince” into the movie. The researcher used qualitative descriptive method. Reading the novel, watching the movie, and note taking record all data from novel and movie were the data collected by the researcher. The researcher used the validity triangulation data and triangulation theory to check validation. The result of the research showed that form of ecranizationdivided into three aspect, namely, shrinkage aspect, additional aspect, and changes variation aspect each of which occurs in the plot, character, and setting. Key Words: Ecranization, The Frog Prince Movie, Qualitative method, Descriptive qualitative